1980
DOI: 10.1128/jb.143.1.35-42.1980
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxamate-mediated transport of iron controlled by ColV plasmids

Abstract: A new high-affinity system for iron transport, associated with the presence of ColV plasmids, has been detected in Escherichia coli and partially characterized. The presence of such "iron-transport plasmids" in E. coli cells that are defective in enterochelin-mediated transport of iron enabled them to grow in media to which 2,2'-dipyridyl had been added to reduce availability of iron. In addition, the presence of plasmid deoxyribonucleic acid in a mutant defective in enterochelin biosynthesis was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 33 publications
2
40
0
Order By: Relevance
“…Both species of Neisseria gave a positive reaction for bound hydroxylamine, indicative of production of hydroxamate siderophores by these microorganisms. Again, the quantity of material produced by the meningococcus was greater than that produced by the gonococcus, although the amount produced by both organisms was considerably lower than that produced by other microorganisms (6,10,26), and it could not be detected in unconcentrated culture supernatant fluids.…”
Section: Resultsmentioning
confidence: 79%
“…Both species of Neisseria gave a positive reaction for bound hydroxylamine, indicative of production of hydroxamate siderophores by these microorganisms. Again, the quantity of material produced by the meningococcus was greater than that produced by the gonococcus, although the amount produced by both organisms was considerably lower than that produced by other microorganisms (6,10,26), and it could not be detected in unconcentrated culture supernatant fluids.…”
Section: Resultsmentioning
confidence: 79%
“…Second, the ColV-B188 plasmid enhanced adhesion in vitro to mouse intestinal epithelium (11). Third, certain CoIV plasmids, but not the ColV,I-K94 plasmid, were found to code for an iron transport system (47,52). Aerobactin was shown to be the siderophore component of this system (50), and the polypeptides involved in aerobactin biosynthesis and transport were identified and mapped by cloning (4; Bindereif et al, submitted for publication).…”
mentioning
confidence: 99%
“…The ability to express the high-affinity system of iron uptake has been correlated with virulence for a variety of microorganisms pathogenic to animals and humans (11). Recently it has been demonstrated that it is the ColV plasmid-directed (12) synthesis in clinical isolates ofEscherichia coli of a hydroxamate-type siderophore (7,13) that accounts, at least in part, for the invasiveness of these organisms. The particular siderophore has been identified as aerobactin (10).…”
mentioning
confidence: 99%